Acceptance and hesitancy of COVID-19 vaccination among Saudi pregnant women - Hawsawi, Sereen; Orabi, Abeer; Alnajjar, Hend (Frontiers in Global Women's Health, 2024)
Introduction: Since COVID-19 pandemic, it has significantly impacted health systems and societies worldwide. Pregnancy increases the risk of severe illness when associated with COVID-19. Pregnant women are likely to experience COVID-19-related pregnancy complications however many of them were hesitant to receive the vaccine. This study aimed to assess the acceptance and hesitancy of COVID-19 vaccination among pregnant women in Jeddah. Methods: The present study utilized a descriptive cross-sectional research design to include pregnant women through convenience sampling at the obstetrics and gynecology outpatient department and antenatal ward at King Abdul-Aziz Medical City, Jeddah. Data was collected from August to October 2022 using a structured questionnaire. Results: Approximately one-third out of the 264 participants (36.4%) strongly disagreed that they had developed immunity against COVID-19. More than half of them 61% and 66.3% respectively had heard that the vaccine was unsafe for them and their babies during pregnancy, and it would contain the COVID-19 virus. However, half of them 50% agreed that vaccination would ease precautionary measures. A high acceptance score toward COVID-19 vaccination was observed among pregnant women working in the health sector. The most frequently reported reason for vaccination refusal was the belief that it was unsafe for the mother and her baby during pregnancy. Conclusion: Most of the participants perceived their susceptibility to COVID-19 infection as low and were hesitant to take the vaccine because of their worry about its effectiveness. However, they indicated a willingness to take the vaccine if it is mandatory and they received adequate information about it.